Ethnic Relations in Plural Societies : Social, Economic and Political Dimensions - Hassankhan, Maurits S.,; Lal, Brij,; Ramsoedh, Hans,; Vahed, Goolam, (Brill | Manohar Publishers & Distributors, 2023)
One of the main legacies of slavery and indentured labour is the existence of multi-ethnic and multicultural societies in former tropical colonies of the European empires. After the abolition of slavery, the indentured labourers were brought to the plantation colonies in order to meet the need for cheap labour for the production of tropical goods. From the beginning, they faced a situation in which they were regarded as competitors for the freed slaves and/or the local population. At the same time, in various cases, the freed slaves and their descendants considered themselves as the indigenous people, and were treated as such by the colonial governments. In their perspective, the colonial governments spent too many resources on the immigration of foreign labourers, resources that could have been used to improve the socio-economic situation of the descendants of the former slaves. To this date, this historical past overshadows the relations between different ethnic groups in so called plural societies. This book deals with the relations between different ethnic groups in these societies and the challenges they meet to establish peaceful and democratic societies. The volume consists of chapters on these societies, such as South Africa, Guyana, Trinidad and Tobago, and Suriname.